(3EeJGY GdCSeGY HeG ddQShd ef GdGHfGA hGdCMhGd hGdMaOI hGdeJGYs - (3CMeO Hf Ydj Hf YHO GdbGOQ, CHh GdYHGS GdMSjfj GdYHjOj, Jbj GdOjf GdebQjRj,J (B845 (3g` s
(3ChdgG (B:s
(3Ydjge hPcQge eY cQGe GdQSd abGd Gddg JYGdi (B" (3bhdhG GefG HGddg heG JQc EdjfG heG JQc Edi GHQGgje hGSeGYjd hGSMGb hjYbhH hGdGSHGW heG ChJi ehSi hYjSi heG ChJi GdfHjhf ef QHge dGfaQb Hjf CMO efge (B" s
(3BNQgG (B:s
(3bGd GHh fYje QhGg Ydi Hf Ydi hMGQLI Hf eUYH Yf GdMQjQi ehdi GdYKef Yf Ce SdeI hGddg GYde ced GdLRA GdKGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B11s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B32 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B886) s
Keywords: (3GdJGQjNs